2010
DOI: 10.1248/bpb.33.844
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator Effect of Cassiarin A, a Novel Antiplasmodial Alkaloid from Cassia siamea, in Rat Isolated Mesenteric Artery

Abstract: Cassia siamea (Leguminosae), a small-to medium-sized tree, is one of the most commonly cultivated trees in Southeast Asia. Different parts of this plant can be used for a variety of medical purposes, giving the plant considerable medicinal potential. In traditional folk medicine, its stem bark is used as a mild, pleasant, safe purgative; a decoction of the bark is given to treat diabetes; a paste is used as a dressing for ringworm and chilblains; the roots are used as an antipyretic; and the leaves are used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…There are few compounds potassium channel activators; cassiarin A being an example of an alkaloid among those (Matsumoto et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…There are few compounds potassium channel activators; cassiarin A being an example of an alkaloid among those (Matsumoto et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The opening of K + channels leads to an efflux of K + that causes the cell membrane to become hyperpolarized, leading to the closure of L-type calcium channels and the reduction of intracellular Ca 2+ [15,16] . In this study, we found that BaCl 2 (an inhibitor of K IR channels) and TEA (an inhibitor of BK Ca channels) remarkably reduced the vasorelaxant effect of ECH, indicating that the K IR and BK Ca channels could be involved in this effect.…”
Section: Discussionmentioning
confidence: 99%
“…These are Cajanus cajan used in cancer treatment [89], Cassia alata used in the treatment of skin diseases such as ringworm, eczema, pruritis, itching, scabies, ulcers and other related diseases, Berlina grandiflora used in the treatment of gastrointestinal disorders, as well as Abrus precatorius and Cassia siamea , both used in the treatment of malaria. A dichloromethane (CH 2 Cl 2 ) fraction of the leaves of Cajanus cajan had IC 50 value 5–10 μg mL −1 , with the two constituent stilbenes, longistylins A ( 78 ) and C ( 79 ), being primarily responsible, with IC 50 values of 0.7–14.7 μM against the range of cancer cell lines [8991]. …”
Section: Fabaceae Ganodermataceae Lamiaceae and Loranthaceaementioning
confidence: 99%